Effects of Bifidobacterium bifidum in Mice Infected with Citrobacter rodentium - Wen, Bijun (Microorganisms, 2019)
In vitro and in vivo studies suggest that selected Bifidobacterium bifidum strains sustain intestinal homeostasis. This study aimed to examine whether the administration of B. bifidum MIMBb75 (BB75) attenuates Citrobacter rodentium infection, a murine model for enteric infection and inflammatory bowel disease in humans. C57Bl6/J mice were randomized to receive BB75 daily starting before or after C. rodentium infection. BB75 load and infection kinetics were monitored. On day 10 post-infection (p.i.), histological parameters of the large intestine were assessed. Barrier integrity was evaluated by pathogen translocation to secondary organs and in vivo permeability test. Fecal C. rodentium load peaked at 10(10) CFU/g at day 10 p.i., with clearance at day 24 p.i., regardless of probiotic treatment. BB75 administration resulted in 10(7) cells/g of feces with no effect of timing of administration. BB75 treatment did not attenuate C. rodentium-induced crypt hyperplasia nor inflammation. C. rodentium and BB75 can co-exist in the gut with no mutual displacement. However, BB75 cannot counteract C. rodentium pathology. Our findings provide insight for the understanding of probiotics behavior and their clinical relevance in intestinal inflammation.